Adaptation of Cheng Beng Tradition in Chinese Confucian Society at the Surakarta Confucian Religious Assembly (MAKIN) - Prastika, Veronica Anggun; Mundayat, Aris Arif; Karono, Drajat Tri Karono (Yayasan Ilomata, 2025)
This study aims to determine the process of adaptation of the Cheng Beng tradition of the Chinese Confucian community at the Surakarta Confucian Religious Assembly (MAKIN). This tradition is one of the pillars of their spiritual cultural identity. Their history has an impact on the Cheng Beng cultural tradition which faces challenges in maintaining its position in a pluralistic environment. This tradition has important meanings and values that are passed down from generation to generation. The novelty of this study raises the issue of pluralism and involves the Confucian Religious Assembly community in Surakarta. This study uses a qualitative method with in-depth interviews and observations. The results found that the adaptation of the Cheng Beng tradition involves driving factors that include local cultural interaction factors, regional geography, family preferences, and modernization. These four factors give rise to a concrete form of the adaptation process in the form of flexibility in the use of offerings and their implementation. Bikhu Parekh's theory regarding the concept of multiculturalism is used to analyze that the adaptation process shows the existence of dynamic cultural pluralism. Because of the interaction between cultures, intercultural dialogue, and recognition of the existence of minority community traditions in the midst of a pluralistic society. This effort is made to create an inclusive society. So that this tradition is relevant and maintained even though there are cultural differences.